Air Change Rates in Multi-Family Residential Buildings in Northern Portugal - Pinto, Manuel (2014)
Existing technical recommendations and standards regarding natural ventilation in Portugal establish one air change rate, ACH, in main rooms (bedrooms and living rooms) and four ACH in service rooms (kitchens and bathrooms). Admittedly these rates are not being observed in most residential buildings recently erected in Portugal. Two trials (May 2002 and January 2003, lasting approximately 2 weeks each) were carried out for the purpose of estimating the implementation of the rates in a two-bedroom flat which is inhabited and equipped with a ‘mixed’ ventilation system: intake via self-adjusting ventilation inlets in the living room and bedrooms, natural exhaust in the bathroom assisted by discontinuous mechanical extraction in the kitchen. Some conclusions can be drawn regarding the efficiency of the ventilation system used, namely the results of the study shows that the measured ventilation rate was irregular and lower than the Portuguese recommendations during both seasons.